Open versus robot‐assisted partial nephrectomy: A longitudinal comparison of 880 patients over 10 years. Issue 1 (21st September 2020) - Zeuschner, Philip; Greguletz, Leonie; Meyer, Irmengard; Linxweiler, Johannes; Janssen, Martin; Wagenpfeil, Gudrun; Wagenpfeil, Stefan; Siemer, Stefan; Stöckle, Michael; Saar, Matthias
Abstract: Background: Most comparisons between robot‐assisted partial nephrectomy (RAPN) and open partial nephrectomy (OPN) indicate the superiority of RAPN, but the learning curve is often not considered. Methods: All consecutive partial nephrectomies from the very first RAPN at a single tertiary referral centre ( n = 818, 500 RAPN vs. 313 OPN) were retrospectively analyzed. Complications, success rates and surgical outcomes were compared. Inequalities between cohorts and the inherent learning curve were controlled by subgroup comparisons, regression analyses, and propensity score matching. Results: Overall, RAPN had fewer complications, less blood loss, and shorter length of stay. However, an inherent learning curve caused higher complications for the first 4 years. Thereafter, perioperative outcomes clearly favoured RAPN, even for more complex tumours. Conclusions: In one of the largest monocentric cohorts over more than 10 years, RAPN was found to be superior to OPN. However, not all advantages of RAPN are immediate because a learning curve must be passed.